THE INFLUENCE OF TSTS LEARNING MODEL ON MATHEMATIC PROBLEM SOLVING OF CLASS VII SMP BUKIT ZAITUN STUDENTS’ KOTA SORONG - Anwar, Zakiyah; Pandegawati, Trian (LPPM Universitas Kahuripan Kediri, 2018)
The aim of this research was to see the influence of TSTS model on problem solving at mathematic students’ class VII of SMP Bukti Zaitun Sorong. This research used pre-experiment research with One Group Pretest-Posttest Design. Population of this research were all students of class VII SMP Bukit Zaitun sorong. The data were counted using one-sample test with the result were thitung= 10,254 > ttabel= 2, 074. Therefore, H0was rejected and Hawas accepted, it meant that there was influence of TSTS models in solving mathematic problem in SMP Bukit Zaitun Sorong. Besides, to see the effect of TSTS in solving mathematic problem, it can be seen from the average score of pre-test and post-test with the KKM score. The average score of before the treatment was 51,46 and was lower than KKM score. The average score of post-test was 76,04 and higher than KKM score. The students respond on the method was 50% positive and and 12,5% was negative. In student observation sheet it found 4,00. This meant that the students were happy and seriously to attend the class. The percentage score of the practical was 84,5%. It can be concluded that TSTS model was successfully used in learning activity Keywords: Problem solving, Learning